Creative writers’ experience of self-determination: An examination within the grounded theory framework - Enko, Jolanta (Thinking skills and creativity, 2014)
•Creativity and self-determination among writers were examined.•The grounded theory approach was used because of its openness to unexpected data.•Self-determination is necessary, yet not sufficient, for creative writing.•The model can serve as a tool facilitating creative performance of creative writers.•The model can be used in fostering creativity in gifted individuals. The aim of this study was to apply grounded theory methodology to an examination of creativity and self-determination among four amateur creative writers. Applying a grounded theory approach to their interview responses, revealed a novel middle-range theory for the role of autonomy. For these respondents, autonomy is necessary, yet not by itself sufficient for their creative writing. A model of self-determination is posited with autonomy as the core category and authorship beliefs and autonomous regulation of the creative process as sub-categories. Based on this model, autonomy-supportive surroundings are reported as positively influencing the development of these respondents' creative talents. Subject to further research, this model may be considered in the design of creativity-fostering environments.